1998
DOI: 10.1083/jcb.143.3.673
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the Kinesin-like Protein Xklp2 to Spindle Poles Requires a Leucine Zipper, a Microtubule-associated Protein, and Dynein

Abstract: Xklp2 is a plus end–directed Xenopus kinesin-like protein localized at spindle poles and required for centrosome separation during spindle assembly in Xenopus egg extracts. A glutathione-S-transferase fusion protein containing the COOH-terminal domain of Xklp2 (GST-Xklp2-Tail) was previously found to localize to spindle poles (Boleti, H., E. Karsenti, and I. Vernos. 1996. Cell. 84:49–59). Now, we have examined the mechanism of localization of GST-Xklp2-Tail. Immunofluorescence and electron microscopy showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
185
1
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 182 publications
(197 citation statements)
references
References 54 publications
8
185
1
1
Order By: Relevance
“…Immunolocalization of the GST-Xklp2 tail on asters was performed as described previously (Wittmann et al, 1998), by using an Alexa red-coupled secondary antibody (Molecular Probes) and visualizing microtubules with Cy-5-labeled tubulin (Hyman et al, 1991). For each experiment, pictures were taken on a Leica TCS Sp2 AOBS confocal microscope at 63ϫ magnification with identical illumination settings and processed identically with Adobe Photoshop.…”
Section: Microscopymentioning
confidence: 99%
See 3 more Smart Citations
“…Immunolocalization of the GST-Xklp2 tail on asters was performed as described previously (Wittmann et al, 1998), by using an Alexa red-coupled secondary antibody (Molecular Probes) and visualizing microtubules with Cy-5-labeled tubulin (Hyman et al, 1991). For each experiment, pictures were taken on a Leica TCS Sp2 AOBS confocal microscope at 63ϫ magnification with identical illumination settings and processed identically with Adobe Photoshop.…”
Section: Microscopymentioning
confidence: 99%
“…Spindles and asters were processed for immunofluorescence as described previously (Wittmann et al, 1998). Immunolocalization of the GST-Xklp2 tail on asters was performed as described previously (Wittmann et al, 1998), by using an Alexa red-coupled secondary antibody (Molecular Probes) and visualizing microtubules with Cy-5-labeled tubulin (Hyman et al, 1991).…”
Section: Microscopymentioning
confidence: 99%
See 2 more Smart Citations
“…NuMA binds microtubules directly and plays a critical role in zippering microtubules into focused poles (Merdes et al 1996(Merdes et al , 2000Silk et al 2009). Similarly, TPX2 binds to microtubules and tends to concentrate at the spindle poles (Wittmann et al 1998(Wittmann et al , 2000. It has been shown that TPX2 is required for microtubule nucleation as well as spindle pole organization (Gruss et al 2002;Garrett et al 2002;Schatz et al 2003).…”
mentioning
confidence: 99%